(untitled) (Research, Society and Development, 2020)
The article aims to develop an analysis of the dialogue conversations about sex and sexuality among teenagers and adolescents people and to spread knowledge about the subject in society, in the light of public health and the human and sexual rights of young people. From this angle, two questions of interviews with teenagers and adolescents people from a state and technical school in Teresina-Piauí were carried out, transcribed and analyzed to understand: what they talk and talk about sex with friends, parents and / or with teachers and the dialogue on sex and sexuality is considered important. The methodology used was a qualitative research, the information was collected through semi-structured interviews and was based on an interpretative analytical study carried out from August to December 2019, in a public technical school, located in Teresina, capital of the Piauí, Northeast Brazilian region. This article focused on eight students, five students aged between 16 and 18 years old and three students aged between 17 and 18 years old. The results point out the doubts, fears and constraints that teenagers and adolescents people go through during the initiation of sexual life, as a result of the social construction that is guided by classist, sexist, homophobic, adult-centric and heteronormative ideologies.